Climatic significance of modern minute land snail shells δ13C and δ18O on the Chinese Loess Plateau. (December 2022) - Zong, Xiulan; Song, Yougui; Dong, Jibao; Li, Yue; Liu, Weiguo; Cao, Yunning; Xing, Meng; Liu, Huifang; Hu, Jing
Highlights: δ 13 C of minute land snail shell could record the local vegetation signals. Shell δ 13 C has the potential to be a reliable precipitation proxy. Spatially scattered shell δ 18 O reflects the dominant control of precipitation δ 18 O. Abstract: Land snails are abundant and well preserved in loess-paleosol sequences on the Chinese Loess Plateau (CLP) and are often regarded as valuable climatic indicators in paleoclimate reconstruction. To date, many stable isotope investigations have been carried out on land snail shells (e.g., δ 13 Cshell and δ 18 Oshell ) from diverse geographical and climatic regions. However, few studies have been conducted on modern minute land snails (2–10 mm) on the CLP, and their climatic significance has not been adequately understood. Here, we present new δ 13 Cshell and δ 18 Oshell data from four minute modern land snails ( Pupilla aeoli, Gastrocopta armigerella, Opeas striatissimum, Vallonia tenera ), and analyses of their correlations with climatic factors (growing season temperature, precipitation and relative humidity) were conducted to examine their climatic significance across the CLP. The results show that δ 13 Cshell can record local vegetation information and has the potential to be a reliable precipitation proxy. Interestingly, δ 18 Oshell exhibits spatially scattered values in the studied region, and these data yielded poor correlations with various climatic parameters, such as precipitation amount, temperature and relative humidity. Given the similar spatial characteristics of observed precipitation δ 18 O (δ 18 Op ), these phenomena may support the dominant control of δ 18 Op on δ 18 Oshell .